Identification and purification of a Bombyx mori homologue of FTZ-F1. - Ueda, H (1990)
Extracts from embryos and from posterior and middle silk glands of the silkworm, Bombyx mori contain a sequence specific DNA binding factor termed BmFTZ-F1. The factor binds to the recognition site of FTZ-F1, a positive regulator of the fushi tarazu gene in Drosophila melanogaster. BmFTZ-F1 and FTZ-F1 share the same methylation interference patterns, the same chromatographic behaviors and similar protease digestion profiles. Anti-FTZ-F1 cross reacts with BmFTZ-F1. These results indicate that BmFTZ-F1 is a B. mori homologue of FTZ-F1. The mobility of the factor-DNA complex formed in the silk gland extract changes depending on the developmental stages. Purification of BmFTZF1 to an almost homogeneous state reveals that the factor is a 73 kd protein.